Smith, Hogan, and Ormerod's : CRIMINAL LAW - Ormerod, David, 1966-; Laird, Karl (Oxford : OXFORD UNIVERSITY PRESS, 2018)
Smith, Hogan, & Ormerod's Criminal Law is rightly regarded as the leading doctrinal textbook on criminal law in England and Wales. Published in its first edition over fifty years ago, it continues to be a key text for undergraduates and an essential reference source for practitioners
Includes index
Keywords: Criminal law -- England; Criminal law -- Wales